WILLY WONKA’S SCHIZOTYPAL PERSONALITY DISORDER IN ROALD DAHL’S CHARLIE AND THE CHOCOLATE FACTORY - NOVI ANDRAWATI (LITERA KULTURA : Journal of Literary and Cultural Studies, 2019)
This study analyse Willy Wonka’s schizotypal personality disorder in Roald Dahl’s Charlie and the Chocolate Factory. Schizotypal personality disorder are subtype from personality disorder that characterized by peculiar,eccentric in thinking and style, difficult in interaction in social and close relationship. This study concern to analyse Willy Wonka character and his schizotypal personality disorder. Dahl describe the character as support character that have prominent personality. The aims of this study is to reveal the schizotypal personality disorder that depicted in Willy Wonka’s character. The first objective of this study is to identify the schizotypal personality disorder that depicted in in Willy Wonka’s character. Then, the second objective of this study is to identify the impact of schizotypal personality disorder in Willy Wonka’s character toward his life and people around him. This study use theory of personality disorder and theory of schizotypal personality disorder by Theodore Millon to reveal the depicted and the impact of schizotypal personality disorder in Willy Wonka’s character from the novel Charlie and the Chocolate Factory. The method use qualitative method and critical interpretation to analyse the data. The result shows that Willy Wonka has schizotypal personality disorder symptom in his personality and behaviour, for instance, Willy Wonka tends to eccentric and odd in his style and his act, Willy Wonka has odd style thinking and speech, Willy Wonka are paranoid person and uncomfortable in social situation. There are some impact that caused by Willy Wonka’s schizotypal personality disorder, for instance his behaviour and personality hard to understand and seems too odd. Wonka make people around him feel conscious and dejected with his behaviour. Penelitian ini menganalisis gangguan kepribadian schizotypal Willy Wonka dalam novel Charlie and the Chocolate Factory. Gangguan kepribadian schizotypal adalah subtipe dari gangguan kepribadian yang ditandai dengan kepribadian aneh, eksentrik dalam berpikir, sulit dalam interaksi dalam hubungan sosial dan tertutup. Penelitian ini bertujuan untuk menganalisis karakter Willy Wonka dan gangguan kepribadian schizotypalnya. Roald Dahl menggambarkan karakter Willy Wonka sebagai karakter pendukung yang memiliki kepribadian menonjol.Tujuan penelitian ini adalah untuk mengungkapkan gangguan kepribadian schizotypal yang tergambar dalam diri Willy Wonka. Tujuan pertama dari penelitian ini adalah untuk mengidentifikasi gangguan kepribadian schizotypal yang digambarkan dalam karakter Willy Wonka. Kemudian, tujuan kedua dari penelitian ini adalah untuk mengidentifikasi dampak gangguan kepribadian schizotypal dalam karakter Willy Wonka terhadap kehidupan dan orang-orang di sekitarnya. Penelitian ini menggunakan teori gangguan kepribadian dan teori gangguan kepribadian schizotypal oleh Theodore Millon untuk mengungkapkan gambaran dan dampak gangguan kepribadian schizotypal pada karakter Willy Wonka dari novel Charlie and the Chocolate Factory. Metode ini menggunakan metode kualitatif dan interpretasi kritis untuk menganalisis data. Hasil penelitian menunjukkan bahwa Willy Wonka memiliki gejala gangguan kepribadian schizotypal dalam kepribadian dan perilakunya, misalnya, Willy Wonka cenderung eksentrik dan aneh dalam gaya dan perilakunya, Willy Wonka memiliki pemikiran dan gaya yang aneh, Willy Wonka adalah orang yang paranoid dan tidak nyaman. dalam situasi sosial. Ada beberapa dampak yang disebabkan oleh gangguan kepribadian schizotypal Willy Wonka, misalnya perilaku dan kepribadiannya sulit dipahami dan tampak terlalu aneh. Wonka membuat orang di sekitarnya merasa marah dan kesal dengan perilakunya.